Distributional Effects of Monetary Policy - Bonifacio, Valentina (IMF Working Papers; Working Paper ;, 2021)
As central banks across the globe have responded to the COVID-19 shock by rounds of extensive monetary loosening, concerns about their inequality impact have grown. But rising inequality has multiple causes and its relationship with monetary policy is complex. This paper highlights the channels through which monetary policy easing affect income and wealth distribution, and presents some quantitative findings about their importance. Key takeaways are: (i) central banks should remain focused on macro stability while continuing to improve public communications about distributional effects of monetary policy, and (ii) supportive fiscal policies and structural reforms can improve macroeconomic and distributional outcomes.